2021
DOI: 10.1177/00031348211038588
|View full text |Cite
|
Sign up to set email alerts
|

Operative Confidence Among U.S General Surgery Residents

Abstract: Background General surgery residents (GSRs) must develop operative autonomy skills to practice independently after graduation. We aim to investigate perceived confidence and operative autonomy of GSR physicians in order to identify and address influential factors. Methods A 28-question anonymous online survey was distributed to 23 United States general surgery residency programs. Multivariable logistic regression was used for calculating the adjusted odds ratio (aOR) for binary outcomes. Significance was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…On the other hand, Sellers et al demonstrated that university-based residencies had higher surgical volume than non-university-based residencies but there was no difference in mortality or complications after matching the cohorts ( 15 ). Elkbuli et al showed that operative confidence increased during residency when residents had a higher surgical case volume ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Sellers et al demonstrated that university-based residencies had higher surgical volume than non-university-based residencies but there was no difference in mortality or complications after matching the cohorts ( 15 ). Elkbuli et al showed that operative confidence increased during residency when residents had a higher surgical case volume ( 16 ).…”
Section: Discussionmentioning
confidence: 99%